The implementation of design and build procurement approach in local construction industry - 399392 Pang, Sheh Haur (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Master of Engineering (Civil - Construction and Management)) - Universiti Teknologi Malaysia, 2004